Teaching English Vocabulary for Young Learners Using Electronic Word Gueesing Game - Anggraini Anggraini (VELES Voices of English Language Education Society, 2021)
Teaching English in this Pandemic period requires an interesting method and teaching Vocabulary using Educational games for young learners becomes interesting. This study aims to describe the application of electronic word guessing game, students' vocabulary mastery, and achievement motivation after the implementation of educational games. Researchers collect research data through observation, interviews, questionnaires, and tests. The results showed that: the benefits of implementing electronic word guessing game were: Making the learning process fun; it activates students to engage; it integrates pronunciation and meaning; it helps students to memorize vocabulary. This research was also conducted to find out the students’ vocabulary mastery before and after electronic word guessing game implementation. The result of the pre-test and post-test show that the students’ mean score on the pre-test was 6.00 and it improved to 7.50 on the post-test. While the problems are: the need for adequate facilities and some technical obstacles that occur during its implementation. And most of the students are very interested in learning vocabulary using electronic word guessing game..